Wisdom Leadership and Its Role in Enhancing the Internal Innovation Performance In the Banking Sector - Haseba Hamad; Yousif Maghdid (Eurasian Journal of Management & Social Sciences, 2022)
Service innovation is critical to organizations’ success in a competitive marketplace, where customers increasingly demand better services. This study aims to investigate if and how wisdom leadership helps organizations increase service innovation performance. The study questionaries were conducted with 191 participants in the 30 different private bank sectors in Erbil, KRI. The conceptual framework of this study led to three main hypotheses and subhypothesizes; our analysis showed positive correlations between wisdom leadership and, service innovation performance and significant impacts on each one. According to this thesis’s data analyses, Banks will get the highest point of service innovation performance through cultivating wisdom leadership in the workplace in which enhances well-being among employees.